PENGARUH MASA FERMENTASI KOPI TERHADAP KARAKTERISTIK AMERICANO - Muhammad Hijriyahntama Wirza Vyanth; Wahyudi Ilham (Puslitabmas Batam Tourism Polytecnic, 2023)
Drinking is a basic human need. The need for this mineral is not only for quenching thirst. These days, there are many different types of drinks on sale, including refreshing and healthy drinks. A probiotic drink is a drink made by adding beneficial bacteria to produce compounds that maintain human health. In this study, we will experiment with the difference in fermentation time between 7 days and his 14 days Americano his coffee fermented with cultures of bacteria and yeast. The tests conducted are sensory tests on her four dimensions of hedonicity (similarities) and hedonic quality (differences) using moderately trained and untrained panelists.color, aroma, texture and taste. The required number of candidates is 20 untrained candidates for the hedonic test and 6 moderately trained candidates for the hedonic quality test. The purpose of this study is to increase our knowledge that bacterial addition can be applied to different types of beverages. Research has shown that a fermentation period of 14 days seems very reasonable.